Oral healthcare providers play a vital role in vaccination efforts: Patient perspectives - Sara Steinbaum; Julia Jagannath; Lake Seymour; Patricia Corby; Roopali Kulkarni; Katherine France (Wiley, 2023)
Abstract Objectives Human papillomavirus (HPV) is associated with 70% of oropharyngeal squamous cell carcinomas. Coronavirus disease 2019 (COVID‐19) is the infectious cause of a global pandemic that killed millions worldwide. Effective vaccinations exist against both diseases, but patient acceptance remains a challenge. The objective of this study was to assess patients' attitudes toward oral healthcare providers' (OHCPs) roles in HPV and COVID‐19 vaccinations. Methods A cross‐sectional survey of young adult patients was distributed in Philadelphia, PA, between April and June 2021. The survey assessed knowledge and attitudes around OHCPs serving various roles in COVID‐19 and HPV vaccination. Results Nearly 70% of 163 respondents would accept the recommendation for a COVID‐19 vaccine from an OHCP, while 56% would for HPV. Those previously vaccinated against COVID‐19 were more comfortable discussing COVID‐19 vaccines (92%, p < .001) or HPV vaccines (76%, p < .001) with OHCPs compared to those who were unvaccinated against COVID‐19. African American/Black patients were less comfortable discussing vaccines, irrespective of vaccination status. Conclusions OHCP can play a vital role in increasing the overall COVID‐19 and HPV vaccination status of the public, as demonstrated by the high acceptance of dental involvement in both vaccine campaigns. Racial disparity in vaccination attitude is a public health challenge that needs to be addressed.